2019
DOI: 10.1186/s40561-019-0095-0
|View full text |Cite
|
Sign up to set email alerts
|

Learning isolated polysemous words: identifying the intended meaning of language learners in informal ubiquitous language learning environments

Abstract: A growing number of language learners use ubiquitous language learning applications to learn anytime and anywhere. Learners translate and learn isolated words inspired by their activities and surroundings. However, isolated words may have several meanings that change depending on the context. Since learners don't have the opportunity to indicate the meaning they are looking for in an online learning environment, they risk learning translations that do not correspond to their intended meaning. Identifying the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The prevalence of polysemy in the English language inspired the present study. Numerous studies, such as Durkin and Manning (1989) and Abou-Khalil et al (2019), have shown that over forty percent of English words are used with more than one meaning. These polysemous words are significant because they are in the top 3000 most often-used words in the English language (Makni, 2013;Ferrer-i-Cancho, 2014).…”
mentioning
confidence: 99%
“…The prevalence of polysemy in the English language inspired the present study. Numerous studies, such as Durkin and Manning (1989) and Abou-Khalil et al (2019), have shown that over forty percent of English words are used with more than one meaning. These polysemous words are significant because they are in the top 3000 most often-used words in the English language (Makni, 2013;Ferrer-i-Cancho, 2014).…”
mentioning
confidence: 99%